VD_FINDINFO HC / 2009 / 387 vom 30. September 2009 - VD Tribunal cantonal (2009)
SUCCESSION, ACTION EN PARTAGE SUCCESSORAL, CONTRAT DE MARIAGE, DROIT ÉTRANGER, USUFRUIT, PROPRIÉTAIRE | 604 al. 1 CC, 569 al. 2 CPC, 54 LDIP, 55 LDIP, 90 LDIP, 92 LDIP